Traffic Accidents on the Hetauda-Narayangarh Road: Promoting Safer Roads for the Sustainable Development Goals (SDGs) - Ghimire, Subarna Prasad (Academia Journal of Humanities & Social Sciences, 2025)
This study investigates the causes of traffic accidents along the Hetauda-Narayangarh route in Nepal from the drivers' perspectives. The study emphasizes that addressing driver-related errors and enhancing infrastructure, education, and community collaboration are essential for ensuring road safety and supporting sustainable development in Nepal. The key findings indicate that driver-related errors, such as reckless driving and speeding, account for approximately 80% of accidents, with distractions—particularly the mobile phone use and fatigue—playing a critical role in the diminished driving performance. The study utilized a structured questionnaire distributed to 100 drivers, yielding 80 valid responses that were analyzed using SPSS version 27. The results suggested that adverse weather conditions, especially light rain and fog, exacerbate accident risks, making road signage, and driver education imperative. While most respondents reported the regular vehicle maintenance, there remains a notable lack of formal driver training, with 95% indicating prior untraining; this points to a crucial need for educational initiatives. In conclusion, enhancing road safety along the Hetauda-Narayangarh corridor necessitates improved infrastructure, consistent vehicle checks, and strategic driver education efforts, fostering collaboration among the government, community stakeholders, and the driving population to minimize accidents. The study sets a foundation for future research aimed at improving transportation safety in the similar contexts.